﻿Zusammenhang zwischen Sarkopenie und Knochendichte – eine Querschnittsuntersuchung mit Männern 72 Jahre + mit Sarkopenie - Kemmler, Wolfgang; Straub, Regina; Kohl, Matthias; von Stengel, Simon (Osteologie, 2019)
Introduction There is some evidence that due to muscle-bone interaction, Sarcopenia might be closely related to Osteopenia and Osteoporosis in older people. The objective of the present article was thus to (1) determine the association between Sarcopenia criteria and bone mineral density (BMD), (2) to determine differences in BMD between Pre-Sarcopenia and Sarcopenia and (3) to consider whether there is an increased risk of Osteopenia and Osteoporosis in community dwelling older men with Sarcopenia. Methods Seventy-eight community dwelling men 72 years and older with Pre-Sarcopenia or Sarcopenia (39 each) according to the 2010 European Working Group on Sarcopenia in Older People (EWGSOP-I) were included in the study. Stepwise multivariate regression analysis was conducted to determine the relative contribution of sarcopenia criteria (ie. skeletal muscle mass index, handgrip-strength, habitual gait speed) on BMD of the lumbar spine (LS) and total hip (tHip) area. Further, differences in BMD-LS and tHip were compared between men with Pre-Sarcopenia and Sarcopenia. Osteopenia (-1.0 to -2.5 standard deviations (SD) T-Score) and Osteoporosis (≥ 2.5 SD T-Score) were defined according to WHO. Results We observed a low but significant explanatory contribution of fat free mass (r 2 =.06, p =.001) and body fat rate (r 2 =.04, p =.011), both positively associated with the BMD of the total hip. Apart from habitual gait speed (r 2 =.03, p =.113) no further parameters contributed to the final model of BMD-LS. Differences in BMD at the tHip or LS were not determined when comparing men with Pre-Sarcopenia versus Sarcopenia (p ≥.95). Further, we did not observe a higher prevalence for Osteopenia or Osteoporosis in the present cohort. Conclusion In summary, the association of parameters presently representing Sarcopenia and Osteoporosis was quite weak in this cohort. Thus, we conclude that at least in community-dwelling men 72 years and older with Sarcopenia according to the EWGSOP-I definition there is no relevantly increased risk of osteopenia and osteoporosis. However, it is doubtful whether this result can be transferred to corresponding older women or institutionalized older people.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Bone Mineral Density; community dwelling; older men; Osteoporosis; Sarcopenia